Reengaging the prospects of rhetoric : current conversations and contemporary challenges - Porrovecchio, Mark J. (Routledge, 2010)
Reanimates the debate over the function and scope of rhetoric. This volume addresses the challenges facing the study of rhetoric. It is useful in undergraduate and graduate courses in the history, theory, and criticism of rhetoric or contemporary rhetorical theory.